PERSPEKTIF HUKUM PROGRESIF PENANGANAN PERKARA PERTANAHAN BERDASARKAN PERATURAN PERUNDANG-UNDANGAN TERKAIT SERTIFIKASI HAKIM DIBIDANG PERTANAHAN - Kiki Nasir Hadi; Khalimi, Khalimi; Achmad Fitrian (Bajang Institute, 2025)
Land issues in general are about disputes over land rights. Disputes over land rights are currently growing along with the emergence of problems in society, especially for justice seekers related to decisions regarding land accompanied by various existing laws and regulations that are not sufficient to answer all land problems that are developing rapidly. To address these problems, the role of jurisprudence is needed as a legal instrument in order to maintain legal certainty, because law is dynamic, both in the normative sense and in terms of activity, both theoretically and practically.Identification in this study is as follows: 1). Is it important to establish the certification of judges who handle land disputes in the modern era in accordance with applicable laws and regulations? 2). What are the next steps to produce professional judges in the field of land if you have not succeeded in realizing the establishment of certification in accordance with the applicable laws and regulations?In accordance with the background and identification of the problem, the aims of this research are: 1). To find and analyze the importance of establishing the certification of judges who handle land disputes in the modern era in accordance with applicable laws and regulations. 2). To find and analyze future steps to produce professional judges in the land sector if they have not succeeded in realizing the establishment of certification in accordance with applicable laws and regulations.This research is normative legal research, normative legal research in this research is based on secondary data and emphasizes speculative-theoretical steps and normative-qualitative analysis. The research approach used by researchers is a qualitative approach, the qualitative approach referred to is a process analysis approach of deductive and inductive thinking processes related to the dynamics of the relationship between observed phenomena.In the context of land dispute resolution, even though in practice the existing laws and regulations are not sufficient to answer all land issues that are developing rapidly, to address these problems, the role of jurisprudence is needed as a legal instrument in order to maintain legal certainty, because law is dynamic. either in a normative sense or in terms of activity, both theoretically and practically. Steps to improve the judicial power system that is independent and accountable, need encouragement from various parties to encourage and maintain the process of reforming the judicial power system through the establishment of certification of judges who handle land disputes according to laws and regulations.